MANAJEMEN PERPUSTAKAAN SEKOLAH DASAR - Apriyani, Desi; Harapan, Edi; Houtman, Houtman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This study determined the management of the SD Negeri 10 Indralaya Utara library. Sources of data in this study were principals, teachers, librarians and students in SD Negeri 10 Indralaya Utara. Data collection techniques observation, interview, documentation. Data analysis techniques 1) data reduction, 2) data presentation, and 3) data verification. The results showed that the four management components carried out by the SD Negeri 10 Indralaya Utara Library Manager well. It is known 1) the management of the SD Negeri 10 Indralaya Utara Library good; 2) the management of the SD Negeri 10 Indralaya Utara Library in terms of organization good; 3) SD Negeri 10 Indralaya Utara Library Management in terms of deployment very good; 4) SD Negeri 10 Indralaya Utara Library Management in terms of supervision very good.